Use of Multiple Methods to Estimate Walrus (Odobenus rosmarus rosmarus) Abundance in the Penny Strait-Lancaster Sound and West Jones Sound Stocks, Canada - Stewart, Robert EA; Born, Erik W; Dunn, J Blair; Koski, William R; Ryan, Anna K (NAMMCO Scientific Publications, 2014)
Surveys to estimate walrus abundance at terrestrial haulout sites in the Penny Strait-Lancaster Sound (PS-LS) and West Jones Sound (WJS) stocks were conducted in 1977 and 1998-2009. The Minimum Counted Population (MCP) was similar in 1977 (565) to recent years (557) for the PS-LS stock. The MCP for the WJS stock was higher in recent surveys (404) than in 1977 (290). Regression analysis of MCP and density (number of walrus divided by number of haulouts surveyed) showed no significant trends over time. We also calculated bounded count estimates for comparison. Finally, we used broad-scale behavioural data to estimate the proportion of the total stock that could be considered countable, to produce two adjusted estimates. We selected recent surveys with good coverage and ignored adjusted estimates that were lower than MCP. For the PS-LS stock, the adjusted MCP (with 95% CL) was 672 (575-768) and 727 (623-831) walrus in 2007 and 2009, respectively. For WJS, the best estimates were the adjusted MCP of 503 (473-534) in 2008 and the adjusted bounded count of 470 (297-1732) in 2009. While both stocks appear to have remained stable over three decades, differences in survey coverage and possible differences in walrus distribution make precise population estimation difficult.